The Cognitive Significance of Language Proficiency Zeal - Zafar Tillaev Akmalovich (Genius Journals, 2023)
One of the interpretations is a cognitive ability a person, which is realized at different levels of the language system, associated with the formation and expression of certain knowledge about the world. This knowledge underlies human cognitive activity, which focused on establishing the cognitive significance of language proficiency zeal, its information content. In a broad sense, cognitive activity is an activity as a result of which a person comes to a specific decision and knowledge, i.e. thinking agent ness, leading to understanding (interpretation) of something
Keywords: cognitive activity; interpretation; knowledge